Exploring Assistant Principals' Views on Parental Involvement in Bahraini Primary Education - Osama Al-Mahdi (Gulf Education and Social Policy Review)
Abstract This study explores assistant principals' views on parental involvement in Bahraini primary education. Through a qualitative approach and interpretive case-study design, this study aims to achieve better understanding of school assistant principals' experiences and their role in facilitating parental involvement in children's schooling through exploring potential benefits, challenges, and issues concerning home–school relations. The theoretical framework of the study is based on the model used by (Epstein, 2011). Data were collected through semi-structured qualitative interviews conducted with eight female Bahraini public school assistant principals who served as key informants. The findings demonstrate the importance of home–school relations and provide examples of how different approaches to home–school relations are used in various schools. The study discusses some of the challenges that impede the involvement of parents in schools and suggests strategies to improve policies and practices related to home–school relations.